A new human-computer interaction paradigm: Agent interaction model based on large models and its prospects - Yang LIU (Virtual Reality & Intelligent Hardware)
This study examines the advent of agent interaction (AIx) as a transformative paradigm in human-computer interaction (HCI), signifying a notable evolution beyond traditional graphical interfaces and touchscreen interactions. Within the context of large models, AIx is characterized by its innovative interaction patterns and a plethora of application scenarios that hold great potential. The paper highlights the pivotal role of AIx in shaping the future landscape of the large model industry, emphasizing its adoption and necessity from a user's perspective. This study underscores the pivotal role of AIx in dictating the future trajectory of a large model industry by emphasizing the importance of its adoption and necessity from a user-centric perspective. The fundamental drivers of AIx include the introduction of novel capabilities, replication of capabilities (both anthropomorphic and superhuman), migration of capabilities, aggregation of intelligence, and multiplication of capabilities. These elements are essential for propelling innovation, expanding the frontiers of capability, and realizing the exponential superposition of capabilities, thereby mitigating labor redundancy and addressing a spectrum of human needs. Furthermore, this study provides an in-depth analysis of the structural components and operational mechanisms of agents supported by large models. Such advancements significantly enhance the capacity of agents to tackle complex problems and provide intelligent services, thereby facilitating a more intuitive, adaptive, and personalized engagement between humans and machines. The study further delineates four principal categories of interaction patterns that encompass eight distinct modalities of interaction, corresponding to twenty-one specific scenarios, including applications in smart home systems, health assistance, and elderly care. This emphasizes the significance of this new paradigm in advancing HCI, fostering technological advancements, and redefining user experiences. However, it also acknowledges the challenges and ethical considerations that accompany this paradigm shift, recognizing the need for a balanced approach to harness the full potential of AIx in modern society.